The association between fever in the first year of life and atopy in children with or without family history of atopic disease - Susy P. Wihadi; Budi Setiabudiawan; Cissy B. Kartasasmita (Indonesian Pediatric Society Publishing House, 2007)
Background The role of repeated infection in early life in the development of childhood atopy is still controversy. Fever in the first year of life which is frequently associated with infections might decrease atopy. Objective The aim of this study was to investigate the association between fever in the first year of life and atopy in children. Methods This was an observational clinical epidemiology study performed at Puskesmas Garuda, Padasuka, and Babakan Sari, Bandung, from January to March 2006. From 749 children, we randomly chose 150 subjects each from group with and without family history of atopic disease. Skin prick test and measurement of total serum immunoglobulin (Ig) E were performed on each children. Atopy was defined as the skin prick test result was positive to >1 allergen. The number of fever episodes in the first year of life was based on parents report. The relationship between fever and atopy was analyzed using Mantel Haenszel. Results From 284 subjects, atopy was found in 28.2% of children, of which 32.4% with and 23.9% without a family history of atopic disease. Generally there was no significant association between fever and atopy. There was only decreased odds ratio with increased fever episodes and trend analysis showed this decrease was significant (P=0.01). The significant association between fever and atopy were found only in group without family history of atopic disease (P=0.03, OR=0.43, CI 95% 0.18;1.01). Conclusion There is a relationship between fever and atopy in children without family history of atopic disease.